Assessing the Potential Usages of Blockchain to Transform Smart Bangladesh: A PRISMA Based Systematic Review - Bhuiyan, Mohammad Rakibul Islam; Akter, Most. Sadia (Universitas Bina Darma, 2024)
In recent years, both researchers and internet users have been attracted to the concept of blockchain technology for transforming smart Bangladesh. This study focuses on the possibilities of blockchain technology leading to the transformation of Bangladesh into a smart nation. This article also explains the working procedure and potential usage of the blockchain concept in Bangladesh. The study is mainly focused on qualitative approaches. The researcher used the PRISMA 2020 platform to identify and choose relevant studies and reports from indexed publications. As the idea of block chain technology is very new and not being adopted by all the sectors of Bangladesh's economy, that’s why only secondary data were used to conduct the study. The researcher has tried to find the different potential areas of blockchain technology from such developing countries like Bangladesh. The potential areas, such as the supply chain management, voting system, and health care industry, where blockchain can be implemented by introducing different polices and regulations. From the implication point of view, blockchain technology might be implemented to transform smart Bangladesh within 2041 if adequate regulations can be undertaken by concerned authority. This revolutionary technology has great potential and has recently caused upheaval. Based on the descriptive study, some of the relevant recommendations including suggestions for reducing challenges of using blockchain are discussed and future research works can be continued in both academic and business sectors in Bangladesh based on this finding.